2008
DOI: 10.1111/j.1365-2958.2008.06438.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of general and regulatory proteolysis in Bacillus subtilis cells

Abstract: SummaryProtein degradation mediated by ATP-dependent proteases, such as Hsp100/Clp and related AAA+ proteins, plays an important role in cellular protein homeostasis, protein quality control and the regulation of, e.g. heat shock adaptation and other cellular differentiation processes. ClpCP with its adaptor proteins and other related proteases, such as ClpXP or ClpEP of Bacillus subtilis, are involved in general and regulatory proteolysis. To determine if proteolysis occurs at specific locations in B. subtili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 72 publications
10
53
0
Order By: Relevance
“…Because both PatS and HetN contain the RGSGR peptide motif and Golden's group has shown that confinement of PatS to source cells prevents proper heterocyst patterning (7), it seems likely that portions of PatS and HetN that include the RGSGR motif constitute diffusible inhibitory signals. The foci of HetR-GFP fluorescence elicited by RGSGR peptide are strikingly similar to those recently observed when various Clp proteases and their substrates were fused to GFP in Bacillus subtilis and Caulobacter crescentus (17)(18)(19), suggesting that PatS-and HetN-dependent signals may target HetR for transport to, and degradation by, cellular proteases located at discreet positions in the cell. PatSand HetN-dependent decay of HetR is distinct from previously reported HetR-autoproteolysis or HetF-dependent degradation as evidenced by decay of HetR S179N , which is not autoproteolytic (15), and decay of HetR in a hetF-mutant background.…”
Section: Discussionsupporting
confidence: 55%
“…Because both PatS and HetN contain the RGSGR peptide motif and Golden's group has shown that confinement of PatS to source cells prevents proper heterocyst patterning (7), it seems likely that portions of PatS and HetN that include the RGSGR motif constitute diffusible inhibitory signals. The foci of HetR-GFP fluorescence elicited by RGSGR peptide are strikingly similar to those recently observed when various Clp proteases and their substrates were fused to GFP in Bacillus subtilis and Caulobacter crescentus (17)(18)(19), suggesting that PatS-and HetN-dependent signals may target HetR for transport to, and degradation by, cellular proteases located at discreet positions in the cell. PatSand HetN-dependent decay of HetR is distinct from previously reported HetR-autoproteolysis or HetF-dependent degradation as evidenced by decay of HetR S179N , which is not autoproteolytic (15), and decay of HetR in a hetF-mutant background.…”
Section: Discussionsupporting
confidence: 55%
“…We attempted to identify phosphorylation on protein arginine residues in vivo in a B. subtilis wild-type strain with various proteomic approaches, but failed to detect it. However, the YwlE phosphatase had been identified as the cognate McsB phosphatase in vitro and was shown to antagonize the activity of McsB in vivo (8,9,(11)(12)(13). This observation strongly suggests that YwlE may act as a general protein arginine phosphatase so that protein phosphorylation on arginine residues could be more stable and enriched in an ywlE deletion strain.…”
Section: Resultsmentioning
confidence: 85%
“…As noted above, it was reported that YwlE is the cognate phosphatase for the McsB kinase in vitro and also antagonizes McsB activity in vivo (8,9,(11)(12)(13). Consequently, we wondered whether McsB is solely responsible for the arginine phosphorylations detected in the ywlE mutant (Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that the YwlE phosphatase antagonizes McsB in vivo (9,16,22). Accordingly, we were interested in whether YwlE contributes to the regulation of McsB activity.…”
Section: Mcsb Kinase Activity Is Inhibited By Clpc In Vivomentioning
confidence: 99%